PERILAKU PENGGUNAAN INTERNET OLEH REMAJA DI SALATIGA DALAM PERSPEKTIF MEDIA SYSTEM DEPENDENCY THEORY - Dewi Kartika Sari (Universitas Kristen Satya Wacana, 2015)
Study on the behavior of Internet usage lately started a lot done. A study of Internet usage behavior seen in the perspective of the media system dependency theory in Indonesia is still hard to find. For this reason, so this research is done. Taking the subject of research is the empirical data because according to teens, the majority of Internet users are teenagers, so look at the behavior of adolescents within the perspective of the media system dependency theory seems interesting to do.The results showed that at the micro level, respondents chose the television media as the primary medium in bermedia activity, followed by the second after the Internet as a medium of television. But in terms of information retrieval, respondents chose the Internet as the main media in obtaining information, followed by television as a media both in the context of obtaining information. At the macro level, it is known that most respondents lived with the family of batih. In the perspective of the media system dependency an attribute theory, social environment gives influence to the respondents to select the medium used and determine which media are used to meet his needs. Other social systems are assumed to have influence is the participation of respondents in organisations in the school and outside the school. Note that the participation of respondents in organisations in the school and outside the school is a member of these organizations.Keywords: Media, Youth, Social System